Mechanosensory Neuron Aging: Differential Trajectories with Lifespan-Extending Alaskan Berry and Fungal Treatments in Caenorhabditis elegans - Scerbak, Courtney; Vayndorf, Elena M.; Hernandez, Alicia; McGill, Colin; Taylor, Barbara E. (Frontiers in Aging Neuroscience, 2016)
Many nutritional interventions that increase lifespan are also proposed to postpone age-related declines in motor and cognitive function. Potential sources of anti-aging compounds are the plants and fungi that have adapted to extreme environments. We studied the effects of four commonly consumed and culturally relevant Interior Alaska berry and fungus species (bog blueberry, lowbush cranberry, crowberry, and chaga) on the decline in overall health and neuron function and changes in touch receptor neuron morphology associated with aging. We observed increased wildtype Caenorhabditis elegans lifespan and improved markers of healthspan upon treatment with Alaskan blueberry, lowbush cranberry, and chaga extracts. Interestingly, although all three treatments increased lifespan, they differentially affected the development of aberrant morphologies in touch receptor neurons. Blueberry treatments decreased anterior mechanosensory neuron (ALM) aberrations (i.e. extended outgrowths and abnormal cell bodies) while lowbush cranberry treatment increased posterior mechanosensory neuron (PLM) aberrations, namely process branching. Chaga treatment both decreased ALM aberrations (i.e. extended outgrowths) and increased PLM aberrations (i.e. process branching and loops). These results support the large body of knowledge positing that there are multiple cellular strategies and mechanisms for promoting health with age. Importantly, these results also demonstrate that although an accumulation of abnormal neuron morphologies is associated with aging and decreased health, not all of these morphologies are detrimental to neuronal and organismal health.